2021
DOI: 10.3390/cancers13235950
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ovarian Tumor Growth in Wild-Type and Lumican-Deficient Mice: Insights Using Infrared Spectral Imaging, Histopathology, and Immunohistochemistry

Abstract: Ovarian cancer remains one of the most fatal cancers due to a lack of robust screening methods of detection at early stages. Extracellular matrix (ECM) mediates interactions between cancer cells and their microenvironment via specific molecules. Lumican, a small leucine-rich proteoglycan (SLRP), maintains ECM integrity and inhibits both melanoma primary tumor development, as well as metastatic spread. The aim of this study was to analyze the effect of lumican on tumor growth of murine ovarian epithelial cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Li et al [ 21 ] discovered that extracellular LUM enhances chemotherapy cytotoxicity in PDAC cells through reduced AMPK activity and inhibition of chemotherapeutic agent-induced autophagy. Nizet et al [ 22 ] showed that LUM primarily inhibits ovarian cancer growth by altering collagen fibrillogenesis. LUM expression differs among tumors and is reported as a reference for tumor prognosis, but its association with tumor progression and treatment resistance varies across tumors [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [ 21 ] discovered that extracellular LUM enhances chemotherapy cytotoxicity in PDAC cells through reduced AMPK activity and inhibition of chemotherapeutic agent-induced autophagy. Nizet et al [ 22 ] showed that LUM primarily inhibits ovarian cancer growth by altering collagen fibrillogenesis. LUM expression differs among tumors and is reported as a reference for tumor prognosis, but its association with tumor progression and treatment resistance varies across tumors [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%
“…Nizet et al [ 22 ] showed that LUM primarily inhibits ovarian cancer growth by altering collagen fibrillogenesis. LUM expression differs among tumors and is reported as a reference for tumor prognosis, but its association with tumor progression and treatment resistance varies across tumors [ [22] , [23] , [24] ]. No studies have examined the efficacy of LUM and CCRT in CESC.…”
Section: Introductionmentioning
confidence: 99%